2008
DOI: 10.1007/s11199-008-9394-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation in Television Advertisements in Britain and Saudi Arabia

Abstract: This study conducted a content analysis of TV adverts from Channel One in Saudi Arabia and ITV1 in the United Kingdom in 2000-2001. A total of 164 adverts were analyzed from each country. The analysis compared the representation of men and women. Results showed that men and women were equally visually represented as lead characters in advertisements in both countries, but male voice-overs dominated in Saudi advertisements more so than in British advertisements. Women appeared more often in domestic roles and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 45 publications
3
52
2
3
Order By: Relevance
“…However, women remain concentrated in product categories relating to the home, food preparation, personal care and the body, while men are more often seen in advertisements for financial products (Ganahl, Prinsen & Netzley, 2003, US) and non-domestic products, particularly those related to automobiles and sports (Bartsch et al, 2000;Ganahl et. al, 2003;Nassif & Gunter, 2008). Studies also consistently show that men are more frequently depicted as powerful, as leaders and as exercising reasoned authority (Beattie, Khan & Philo, 1998, UK;Coltrane & Messineo, 2000;Seiter, 1995, US), and appear in a wider range of occupational roles than women (Furnham & Mak, 1999;Nassif & Gunter, 2008;Neto & Pinto, 1998, Portugal).…”
Section: Literature Review and Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, women remain concentrated in product categories relating to the home, food preparation, personal care and the body, while men are more often seen in advertisements for financial products (Ganahl, Prinsen & Netzley, 2003, US) and non-domestic products, particularly those related to automobiles and sports (Bartsch et al, 2000;Ganahl et. al, 2003;Nassif & Gunter, 2008). Studies also consistently show that men are more frequently depicted as powerful, as leaders and as exercising reasoned authority (Beattie, Khan & Philo, 1998, UK;Coltrane & Messineo, 2000;Seiter, 1995, US), and appear in a wider range of occupational roles than women (Furnham & Mak, 1999;Nassif & Gunter, 2008;Neto & Pinto, 1998, Portugal).…”
Section: Literature Review and Hypothesesmentioning
confidence: 98%
“…Studies also consistently show that men are more frequently depicted as powerful, as leaders and as exercising reasoned authority (Beattie, Khan & Philo, 1998, UK;Coltrane & Messineo, 2000;Seiter, 1995, US), and appear in a wider range of occupational roles than women (Furnham & Mak, 1999;Nassif & Gunter, 2008;Neto & Pinto, 1998, Portugal). Women are less frequently depicted as professionals or product authorities and remain underrepresented in vocational roles, while being over-represented in maternal, homemaking and aesthetic roles (Furnham & Mak, 1999; see also Furnham & Skae, 1997, UK;Gilly, 1988, Australia, Mexico & US;Nassif & Gunter, 2008;Neto & Pinto, 1998). For example, in their cross-cultural comparative study, Paek, Nelson and Vilela (2011) found that in US and Canadian advertisements men were significantly more likely than women to be depicted as professionals and office workers, while nearly all those depicted as homemakers were women.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Es decir, si bien físicamente la presencia de personajes femeninos es elevada (incluso más elevada que la masculina), los spots de alimentación parecen optar, de forma predominante, por voces masculinas a la hora de ofertar los distintos productos. Coincidimos, así, con estudios empíricos previos (Rausell, González y Ortiz, 2008;Valls y Martínez, 2007;Nassif y Gunter, 2008;Whippe y McManamon, 2002) que sitúan la mayor desigualdad en cuanto a presencia de hombres y mujeres en aquella que toma la forma de narradores y voces over. Más difícil es contrastar los resultados obtenidos con los centrados en los spots de alimentación (Furnham y Li, 2008y Aronovsky y Furnham, 2008; ya que no diferencian entre voces over y protagonistas, analizando ambos caracteres de forma conjunta.…”
Section: Resultados Y Análisisunclassified
“…Físicamente, es más frecuente que aparezcan representadas como "jóvenes adultas, frente a una mayor diversidad, según grupos de edad, a la hora de representar a los caracteres masculinos" (Stern y Mastro, 2004: 216). La presencia de mujeres en los espacios publicitarios sigue siendo inferior a la masculina, sobre todo en la forma de narradores y voces over (Valls y Martínez, 2007;Nassif y Gunter, 2008;Furnham y Farragher, 2001).…”
Section: Género Y Publicidad Televisivaunclassified
See 1 more Smart Citation